A Numerical Simulation on characteristic flow of Ahmed Body Model with Slanted Angle - Syamsuri Syamsuri; Zain Lillahulhaq; Muhammad Abrory (Universitas Sultan Ageng Tirtayasa, 2020)
Simplify car models such as Ahmed body is commonly used in numerical simulation because the aerodynamic forces that occur around the car are well captured. Various conditions around Ahmed body models change aerodynamic condition around the vehicle. Behind Ahmed body model, 2 secondary flow vortices are formed, called the twin vortex. This study explains the effect of various inlet velocities to the aerodynamic forces around the car at various inlet velocities of 35 m / s, 40 m / s and 50 m / s. This research simulate the Ahmed body model in 2D steady with the realizable k-epsiloin turbulence model. The Ahmed body model used in this study has 30o slope angle. At inlet velocity of 40 m / s wake that is formed the smallest size. At the inlet condition 40 m / s fluid flow has enough energy to suppress the wake that forms on the twin vortex and produces a small wake. Fluid flow at the bottom of the vehicle tends to be stable and produces similar trandline at various velocity.